Analysis Of Perceived Quality As A Mediator Between Brand Image And Electronic Word Of Mouth On Brand Loyalty Among Users Of The Originote Skincare Products - Putri, Meylani Yulia; Purwanto, Sugeng; Hadi Raharjo, Raden Johnny (UNIVERSITAS PAKUAN, 2025)
The Originote is a local skincare brand that has been proven to overclaim, but has not experienced a significant decline in sales. The study was conducted with the aim of analyzing the effect of brand image and electronic word of mouth on brand loyalty with perceived quality as a mediating variable, in generation Z users of The Originote skincare in Surabaya City. Quantitative methods are used in this research, involving 114 respondents as samples taken by purposive sampling, and analyzed with SEM-PLS method using SmartPLS 3.0 application. The results showed that brand image has a direct effect on brand loyalty, while electronic word of mouth cannot directly influence brand loyalty. In addition, it is concluded that perceived quality mediates the relationship between brand image and electronic word of mouth on brand loyalty. This research highlights the importance of brand image and perceived quality in maintaining consumer loyalty.